To What Extent Do Organizational Reputation, Personal-Organizational Value Fit, And Perceived Growth Opportunity Influence The Retention Intentions of Millennial Employees in Jakarta's Fintech Sector? - Sakaria, Maulid; Muhtadi, Muhamad Ammar; Bunyamin, Ilham Akbar (Westscience Press, 2025)
This study investigates the influence of organizational reputation, personal–organizational value fit, and perceived growth opportunities on millennial employee retention intentions in Jakarta’s fintech sector. Using a quantitative research design, data were collected through questionnaires distributed to 130 millennial employees working in various fintech companies. Responses were measured on a five-point Likert scale, and the data were analyzed using SPSS version 25 through validity, reliability, classical assumption, and multiple regression tests. The findings show that organizational reputation, value fit, and growth opportunities each have a significant and positive effect on employee retention intention. Among these, perceived growth opportunities emerged as the strongest predictor, indicating that millennials are highly motivated to stay when they perceive clear pathways for professional development and advancement. These results emphasize the importance for fintech firms to strengthen their reputation, foster value alignment, and provide structured career growth opportunities to effectively retain millennial talent. The study contributes to both theory and practice by extending employee retention research into the fintech context of an emerging economy while offering actionable strategies for human resource management.